Development of a Novel Classification technique for detection of Cowpea Leaves using VGG16 Deep Convolutional Network - Choudhary, Vijaya; Guha, Paramita; Tripathi, Kuldeep; Mishra, Sunita (PREPARE@u® | IEI Conferences, 2021)
This paper is based on CNN-VGG16 network architecture in order to identify the cowpea plants from weed in the cowpea fields. It is done to increase the productivity of the crops. The VGG16 is a basic network of Convolutional Neural Network family and it has quite good classification performance. Implement and modification is quite easy with this model. Here, we have applied pre-trained VGG16 method to the cowpea as well as weed leaves custom dataset. Images of leaves have been taken from standard research farm, ICAR-NBPGR, Pusa campus, New Delhi. The dataset includes 1230 images of two classes. The basic principle of VGG16 network for automatic detection includes, feature extraction from input image, addition of convo layer, pooling layer addition, fully connected layer, and sigmoid for classifiers. Results from experiments show that the model efficiently classifies the cowpea and weed images. Here, accuracy rate on the training dataset is 97.58%, and that of test dataset set is 90.08%. Such results give hope for achieving agricultural reforms.